Síndrome da fragilidade como preditora de desfechos adversos em idosos hospitalizados: uma revisão sistemática e metanálise - Cunha, Ana Izabel Lopes (2019)
INTRODUCTION: The frailty syndrome is prevalent in hospitalized older people as well as the occurrence of adverse outcomes. OBJECTIVE: To verify through a systematic review if the frailty syndrome in hospitalized older people predicts adverse outcomes. METHODS: We conducted manual and electronic searches (PUBMED, EMBASE, Web of Science, Lilacs, CINAHL, PsycINFO and Google Scholar), with no language restriction and published since 2001. Prospective observational studies with hospitalized older people (≥ 60 years) evaluated for frailty syndrome at hospital admission were included. Primary outcomes were functional decline at hospital discharge and mortality after discharge. Other data were considered secondary outcomes. The methodological quality of the studies was evaluated by the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. A critical analysis and meta-analysis were performed. RESULTS: 23 articles were included, corresponding to 15 studies. Frailty was evaluated by 11 instruments. Functional decline was assessed by four studies, showing that being non-frail is a protective factor for such outcome compared to being frail [RR: 0.76 (95% CI: 0.60-0.97)]. Mortality after hospitalization was evaluated in 13 studies, with the medium- and long-term risk being lower for both non-frail (mean RR: 0.11 (95% CI: 0.02-0.52) and long- RR: 0.13 (95% CI: 0.08-0.21)] and pre-frail [RR: 0.30 (95% CI: 0.09-0.96) and long-RR: 0, 27 (95% CI: 0.08-0.86)] comparing to frail older people. Frailty is also a predictor of in-hospital mortality and longer hospital stay. The methodological quality of the studies was considered moderate to good. CONCLUSION: Frailty in hospitalized older adults predicts risk for functional decline in hospitalization, longer hospitalization, and higher in-hospital mortality in the medium and long term.